PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MIND MAPPING DENGAN POWERPOINT DI SMA ISLAM TERPADU GRANADA SAMARINDA - Reza Reza; Noor Ellyawati; Rima Masyanah (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2021)
This research is intended to develop learning media, determine the feasibility, and assess the trial of PowerPoint based on mind mapping as a learning media to the students. This research and development uses Luther's Multimedia Development Life Cycle (MDLC) model. In data collection, this research uses observation, questionnaires, and interviews. The assessment of learning media feasibility involves content experts, media experts, and 23 respondents or students of class XI IPS B at SMA Islam Terpadu Granada Samarinda. Qualitative and quantitative data analyses are conducted. The results of this development research are: (1) the usage of Multimedia Development Life Cycle (MDLC) model through the stages of conceptualizing, designing, content collecting, assembling, testing, and distributing. (2) The validation result on PowerPoint based on mind mapping as a learning media by content expert is in the “very feasible” criteria with 4.73 average score in all aspects. The media expert's assessment is in the criteria of "very feasible" with 4.60 average score. In the trial to the students or respondents, the result is included in "feasible" criteria with 3.77 average score.Keywords: learning media, mind mapping, PowerPoint